Enumeration for spanning trees and forests of join graphs based on the combinatorial decomposition - Sung Sik U (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2016)
This paper discusses the enumeration for rooted spanning trees and forests of the labelled join graphs K_m+H_n and K_m+K_n,p, where H_n is a graph with n isolated vertices.